2018
DOI: 10.1002/bmc.4182
|View full text |Cite
|
Sign up to set email alerts
|

A validated LC‐MS/MS method for the determination of senkyunolide I in dog plasma and its application to a pharmacokinetic and bioavailability studies

Abstract: Senkyunolide I is one of the major bioactive components in the herbal medicine Ligusticum chuanxiong. The aim of this study was to develop and validate a fast, simple and sensitive LC-MS/MS method for the determination of senkyunolide I in dog plasma. The plasma samples were processed with acetonitrile and separated on a Waters Acquity UPLC BEH C column (50 × 2.1 mm, 1.7 μm). The mobile phase consisted of 0.1% formic acid aqueous and acetonitrile was delivered at a flow rate of 0.3 mL min . The detection was a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…The blocked hepatic-intestinal circulation may result in more SEI being transported from the liver into the plasma and less into the bile [15] . Moreover, SEI exhibits similar pharmacokinetic and BA profiles in rats and dogs, that is, rapid absorption, rapid clearance, moderate BA, and a dose-independent pharmacokinetic profile, suggesting that this metabolic profile may also be conserved in humans [16] .…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The blocked hepatic-intestinal circulation may result in more SEI being transported from the liver into the plasma and less into the bile [15] . Moreover, SEI exhibits similar pharmacokinetic and BA profiles in rats and dogs, that is, rapid absorption, rapid clearance, moderate BA, and a dose-independent pharmacokinetic profile, suggesting that this metabolic profile may also be conserved in humans [16] .…”
Section: Pharmacokineticsmentioning
confidence: 99%
“…The pharmacokinetic properties of SI have been studied on animals (mice, rats, and dogs) via different administration routes [35,89,90]. The results indicated that SI would be absorbed rapidly followed by short half-life (<1 h) elimination and acceptable oral bioavailability (>35%) after intragastric administration.…”
Section: Pharmacokinetic Properties Of Simentioning
confidence: 99%